Reduction of blood eosinophil counts in eosinophilic chronic rhinosinusitis after surgery. Issue 12 (2nd November 2016) - Honma, A; Takagi, D; Nakamaru, Y; Homma, A; Suzuki, M; Fukuda, S
Abstract: Objective: This study aimed to predict eosinophilic chronic rhinosinusitis prognosis by investigating changes in the blood eosinophil count and other disease biomarkers after surgery. Methods: Blood eosinophil numbers and serum interleukin-5 levels were measured in 22 eosinophilic chronic rhinosinusitis patients before and after functional endoscopic sinus surgery, and compared with equivalent measures in non-eosinophilic chronic rhinosinusitis patients and chronic rhinosinusitis without polyps patients. Differences between well-controlled eosinophilic chronic rhinosinusitis patients and those who experienced recurrence were also assessed. Results: Blood eosinophil numbers and serum interleukin-5 level decreased after surgery in eosinophilic chronic rhinosinusitis patients. In this patient group, blood eosinophil counts before surgery were significantly higher in patients who experienced recurrence (825.7 ± 26.1 vs 443.9 ± 76.6 cells/μl, p < 0.05), and decreased significantly after surgery (825.7 ± 26.1 vs 76.7 ± 25.8 cells/μl, p < 0.05). Conclusion: Blood eosinophil numbers may reflect disease severity in eosinophilic chronic rhinosinusitis patients and their prognosis after surgery.